2016
DOI: 10.2217/rme-2016-0023
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Yield and Neuronal Differentiation of Mesenchymal Stem Cells from Umbilical Cord Blood and Matrix

Abstract: Cell yield is affected by certain donor characteristics. hUCB- and WJ-derived MSCs may serve distinct therapeutic niches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
2
1
0
Order By: Relevance
“…The variation in the migration of cells from the CT and proliferation rate had no correlation with the type of birth, age, or baby weight. This is similar to the result of Rezniczek et al [24] as they also observed that maternal and gestational age did not influence MSC yield but birth weight did. Two studies observed maternal age influenced CD105+ cell yield but they did not have results on overall cell yield [25,26].…”
Section: Discussion Msc's Isolation Efficiency and Characteristicssupporting
confidence: 91%
“…The variation in the migration of cells from the CT and proliferation rate had no correlation with the type of birth, age, or baby weight. This is similar to the result of Rezniczek et al [24] as they also observed that maternal and gestational age did not influence MSC yield but birth weight did. Two studies observed maternal age influenced CD105+ cell yield but they did not have results on overall cell yield [25,26].…”
Section: Discussion Msc's Isolation Efficiency and Characteristicssupporting
confidence: 91%
“…According to [30], the yield of MSCs was not signi cantly affected by the mother's age or gestational age, but a greater birth weight was associated with a more yield, which is consistent with our ndings. On the other hand, [24] found that lower birth weight correlates to higher SOX2 gene expression in WJ-SCs.…”
Section: Discussionsupporting
confidence: 91%
“…According to [30], vaginal and cesarean births had MSC cell yields that were comparable. According to [29], the method of delivery had no impact on the characteristics or survivability of MSCs.…”
Section: Discussionmentioning
confidence: 99%